CPM452 : Photographic imaging application / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
To expose the students on the fundamentals of post-processing studies; assigning the basic usage of the tool to the development of digital workflow. The designed projects or exercises, in which, allows the students a practical in problem solving, with the intention of generating plausible dynamic composition possible within the editorial process and greater understanding in the importance of quality imaging in the pre-process. Students are encouraged to be creative in the usage of art & graphic fundamentals into their composition.